GIMMICK IN THE REALITY SHOW RUMAH UYA - Oktora, Dina Dwika (Seni Media Rekam ISI Surakarta, 2020)
This research focuses on the gimmick in reality television shows, namely the Rumah Uya program which is broadcasted by ANTV station. This research uses a qualitative descriptive approach, data collection uses purposive sampling techniques, and data analysis uses content analysis. The results showed that the gimmick added to this event was not only a sound effect, but also create the acting of talents with dialogues that tended to be vulgar and showed impolite behavior. This contradicts with the applicable broadcasting regulations, namely the policies set out in the Indonesian Broadcasting Commission (Komisi Penyiaran Indonesia) regulation. Adding gimmicks to the reality show program can be done as long as it does not conflict with decency, law, and applicable regulations.